رثاء المدن بالشعر العربي : دراسة جماليةLamenting Cities in Arabic Poetry: An Aesthetic Study (Al-Qamar, 2022)
Lamentation is one of the purposes of ancient Arabic poetry, where we see the art of the ignorant people and this art moved from them to other Islamic ages, where we see poets added what they distinguished in lamenting their dear cities and their kingdoms, where poets did not move away from using rhetorical purposes as a means to show their suffering, because it is a purpose of The truest poetic purposes, as it embodies the human feeling and has sincere affection towards the one who is said about him. Lamentation is based on a characteristic which is the praise of the dead or the collapsed cities, and mentioning his good qualities and qualities that embody his image in the reader. Lamentation is an art linked to daily life and lived reality, since life is full of wars and the consequent loss of relatives and property. War is the main gesture in this art, as it gives the poet connotations of heroism, the experience of death, and the usurped right.
Keywords: Elegy poetry; Cities; lamentation; feelings